Computation of scattering kernels in radiative transfer. (November 2015) - Engler, Hans
Abstract: This note proposes rapidly convergent computational formulae for evaluating scattering kernels from radiative transfer theory. The approach used here does not rely on Legendre expansions, but rather uses exponentially convergent numerical integration rules. The relation between the domain of analyticity of a given phase function and the speed of convergence is studied in detail. Abstract : Highlights: We propose the trapezoidal rule for the computation of scattering kernels. The convergence rate is related to the analyticity of the phase function. This provides a unified rapidly convergent computational approach.